Some Implicatios of the Developments in Eastern Europe for the European Economic and Monetary Union - Giorgio Basevi (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1990)
In this paper I shall try to sketch what could be some important consequences of recent developments in Eastern Europe, for the present fabric of the European Community (EC) and its evolution into a European Economic and Monetary Union (EEMU).
Keywords: 330